Educating force multipliers: constructing terrorism in a US public high school. Issue 6 (2nd November 2018) - Nguyen, Nicole
ABSTRACT: This article ethnographically explores a specialized Homeland Security program at a US public high school, paying careful attention to the program's discursive constructions of terrorism and national security. In particular, this analysis examines how the Homeland Security program framed its study of national security as both anti-racist and objective. I contend that the invocation of anti-racism and objectivity can advance Orientalist discourses in the classroom. Critical education scholars need to address how teachers and students rely on liberal precepts like anti-racism to maintain dominant understandings of war, terror, and security.